Effectiveness of Blood Pressure Reduction Reviewed from Amount of Kop, Duration And Location of Point of Bekam Therapy - Muflih Muflih; Mohamad Judha (Faculty of Nursing, Universitas Jember, 2019)
Hypertension can be treated traditionally with complementary therapies such as cupping therapy. Evaluation of the effectiveness of cupping therapy on blood pressure reduction is thought to be influenced by variations in cupping therapy techniques. The purpose of this study was to prove scientifically the effectiveness of the number of heads, duration and location of cupping therapy points with a decrease in the value of blood pressure in patients at the Klaten Migoenani Health Nursing Clinic. This research method uses the Quasy experimental one group pre post test method. Data from the analysis of blood pressure measurements in patients undergoing cupping therapy were measured with digital tension and a statistical hypothesis test was performed. The sample technique uses quota sampling. The results showed that cupping therapy effectively reduced the average 20 mmHg of systolic and diastolic blood pressure by the number of locations of cupping points 1-3 locations, the number of heads of 18-24 and for 25-30 minutes of therapy through the process of nitrite dioxide stimulation which caused peripheral vasodilation . The conclusion of this study is that variations in blood pressure reduction in cupping therapy can be determined from the number of heads, duration and location of cupping points.